RECURRENT RESUSCITATION PROCEDURES IN PEDIATRIC PATIENTS: A BIOETHICAL DISCUSSION ON DYSTHANASIA - Svaiter Tominaga, Akemi; Júlia Rodrigues Bezamat, Ana; Teixeira Amarante, Bernardo; da Mata Dias Corrêa, Júlia; Melo Dias Neto, Ronaldo; Alt Parente, Elizabeth; Costa Silva, Lays (Health and Society, 2024)
The present study refers to a real case report, in which a bioethical analysis is developed, from the perspective of principlism, in the environment of a pediatric intensive care unit, with the objective of discussing the dysthanasia practiced in the medical setting and the decision-making of those involved in this case. A search was performed in the Scientific Electronic Library Online (SciELO) and PubMed databases for literature review. Dysthanasia consists of a treatment that only prolongs the pain, making any investment in healing an aggression against the dignity of the human person. When the patient is a child close to death, the difficulty for professionals becomes even greater. Therefore, it is necessary to pay greater attention to the curriculum, raising discussions and reflections on the subject, in order to train professionals to deal with finitude and play their role of offering support and comfort, as well as helping families to identify what quality of life means to them and how it is possible to achieve it.